The Effectiveness of Animation Videos and Flashcard Games on Adolescent’s Knowledge about Reproduction Health among Junior Highschool Students - Arip, Moh; Amanda, Aurora; Rusmini, Rusmini; Ramadhan, Sahrir (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2024)
Adolescents face various emotional and social challenges, including increasing reproductive health issues such as unprotected sexual behavior, unintended pregnancies, and sexually transmitted infections. Adolescent reproductive health knowledge is considered insufficient, with the majority of adolescents having inadequate knowledge. Studies indicate that the use of interactive and engaging animation videos and flashcard games can enhance adolescent knowledge. This research aims to examine the effectiveness of Animation Videos and Flashcard Games in Improving Knowledge about Adolescent Reproductive Health among Students of State Junior High School 2 Batu Layar in 2024. The research method usedÂ quasi-experimental design with a non-equivalent two groups design on 51 respondents using Proportionate Random Sampling technique. Animation videos and flashcard games were provided for 3 sessions per week. Data collection on knowledge was conducted using a questionnaire and analyzed using the Wilcoxon Signed Rank Test with a significance level of 95% (Î± = 0.05). Before the intervention, respondents had sufficient knowledge about adolescent reproductive health, with 14 respondents (54%) in the animation video group and 10 respondents (40%) in the flashcard game group falling into the category of insufficient knowledge. After the provision of animation videos, the majority of respondents, 14 individuals (54%), reached the category of good knowledge. Meanwhile, following the use of flashcard games, the results showed that 22 respondents (88%) achieved good knowledge category.There is a difference in the effectiveness of animation videos and flashcard games in improving knowledge about adolescent reproductive health among students of State Junior High School 2 Batu Layar in 2024. Exploring and developing more diverse and engaging educational methods for topics related to reproductive health systems.